1982
DOI: 10.1080/00288233.1982.10420925
|View full text |Cite
|
Sign up to set email alerts
|

Competition and persistence of strains ofRhizobium trifoliiin relation to inoculation level and lime pelleting on white clover sown into cultivated soil

Abstract: Five strains of Rhizobium trifolii were assessed for their ability to compete with naturalised strains in nodulating white clover (Trifolium repens) sown in cultivated soil. At the initial assessment 5 months after sowing, the inoculant strains at the normal rate of slurry-inoculation had formed only a small percentage of the nodules present. Increasing the inoculation level to 10 times normal or lime pelleting increased the percentage of nodules formed by all strains apart from PDDCC 2163, which formed a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…This work reinforces other work (using chromosomal and plasmid restriction fragment length polymorphism) done at the University of Otago, New Zealand, (Elliot 1997;Shah 2003) that demonstrated genotypic variation in rhizobia in New Zealand pastures. In previous surveys, a high titre of naturalized strains has been demonstrated (Greenwood 1965;Hale 1980;Rhys & Bonish 1981;Gaur & Lowther 1982) and this field site is typical of New Zealand lowland soils having a history of inoculation with commercially available strains of rhizobia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work reinforces other work (using chromosomal and plasmid restriction fragment length polymorphism) done at the University of Otago, New Zealand, (Elliot 1997;Shah 2003) that demonstrated genotypic variation in rhizobia in New Zealand pastures. In previous surveys, a high titre of naturalized strains has been demonstrated (Greenwood 1965;Hale 1980;Rhys & Bonish 1981;Gaur & Lowther 1982) and this field site is typical of New Zealand lowland soils having a history of inoculation with commercially available strains of rhizobia.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether the dominant naturalized strains at the Canterbury site could fix N 2 at levels similar to strain WSM1325. Research has shown that the symbiotic effectiveness of naturalized strains varies widely, between 2 and 100% of that demonstrated by highly effective commercial inoculants (Gaur & Lowther 1980, 1982Rhys & Bonish 1981;Svenning et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These populations of Rhizobium trifolii exhibit a wide range of effectiveness (ability to fix nitrogen) with white clover (Greenwood 1%0), and recent surveys (Bonish 1979;Hale 1980;Gaur & Lowther 1980) have shown that the effectiveness of field strains of R. trifolii in both North Island and South Island soils is generally 10-30% below that of commercially available inoculant strains.…”
Section: Introductionmentioning
confidence: 99%
“…The symbiotic effectiveness of Rhizobium trifolii strains isolated from an established white clover (Trtfolium repens L.)/ryegrass pasture over a 3-year period ranged from 24 to 130% of the effectiveness of a commercially recommended strain NZP561 (PDDCC 2163) when tested on 'Grasslands and the naturalised Rhizobium population for nodule formation (Brockwell et al 1980;Hale 1981;Gaur & Lowther 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation